Effect of bronchoconstrictor aerosols on the alveolar plateau of the single breath O2 test. Issue 6 (November 1968) - Stanescu, D. C.; Teculescu, D. B.; Pacuraru, R.; Popa, V.
Abstract : In 17 subjects with bronchial asthma and chronic bronchitis measurements of the uneven ventilation using the single breath oxygen test, F.E.V.1·0 and V.C. were performed before and after acetylcholine or allergen nebulization. An increase of the alveolar slope was noticed in five out of the seven patients with induced bronchospasm and a decrease in the remaining two. In two other subjects moderate dyspnoea not reflected by spirographic tests was accompanied by a definite increase of the N2 gradient. One patient experienced a severe asthmatic attack after acetylcholine without significant increase of the N2 gradient. In the last seven subjects the spirographic tests were not impaired but the N2 gradient rose to a significant level in three. The various implications of these results are discussed. In one subject the alveolar nitrogen concentration decreased after acetylcholine with a concomitant increase in the residual volume. This finding was assumed to be the result of either a failure of inspired oxygen to mix with alveolar nitrogen or a decreased available lung space.